AN INNOVATIVE APPROACH FOR SECURING RFID BASED CARD INFORMATION FROM DIGITAL PICK-POCKETING - DIPANKAR SARKAR; MANISH ROY; SANTOSH DAS (International Journal of Innovations in Engineering Research and Technology, 2018)
With the influence of both the advancement of technology as well as the Government of India’smission is to achieve Digital India, the use of plastic money have increased drastically in these days. As a result, the probability of cyber theft is also increasing proportionately. With the availability of low-cost RFID scanner in the market, card details are more vulnerable to cyber theft. For this reason, our approach is to make a special device whichwill block any unauthorized access of card information wirelessly i.e. it actually ensures the security and confidentiality of the card information as well as it provides the portability of the card also. So, anyone and everyone can easily carry the card and doing their necessary transaction anywhere smoothly.